2018
DOI: 10.1039/c8ra03125h
|View full text |Cite
|
Sign up to set email alerts
|

Direct reaction between silicon and methanol over Cu-based catalysts: investigation of active species and regeneration of CuCl catalyst

Abstract: CuxSiyClz formed at a lower pretreatment temperature favored trimethoxysilane formation while chlorination of spent CuCl/Si mixture promoted the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 19 publications
(14 reference statements)
1
21
0
Order By: Relevance
“…The Cu 3 Si phase is usually formed at temperatures higher than 280 °C. 18 As we have shown previously 10 and in this study, Cu 3 Si is formed under conditions of mechanical activation at a temperature as low as 250 °C. This is an indication that mechanical activation favors the formation of this intermetallide.…”
Section: Reaction Chemistry and Engineering Papersupporting
confidence: 73%
“…The Cu 3 Si phase is usually formed at temperatures higher than 280 °C. 18 As we have shown previously 10 and in this study, Cu 3 Si is formed under conditions of mechanical activation at a temperature as low as 250 °C. This is an indication that mechanical activation favors the formation of this intermetallide.…”
Section: Reaction Chemistry and Engineering Papersupporting
confidence: 73%
“…Due to the presence of a shoulder peak at 574.7 eV, an extra Gaussian−Lorentzian band at 574.7 eV was used to eliminate the effect of other orbital electrons. 40 The strong peak at 525.4 eV and a small peak at 568.0 eV in Cu LMM Auger spectrum confirmed that both Cu 0 and Cu + were present in A-CuNCs-1 as well. On the other hand, the XPS investigation was studied after the introduction of Ce 3+ for A-CuNCs-2.…”
Section: ■ Results and Discussionmentioning
confidence: 61%
“…On the other hand, the peaks for Cu LMM were deconvoluted into two peaks of Cu + and Cu 0 species by using the XPSPEAK41 software. Due to the presence of a shoulder peak at 574.7 eV, an extra Gaussian–Lorentzian band at 574.7 eV was used to eliminate the effect of other orbital electrons . The strong peak at 525.4 eV and a small peak at 568.0 eV in Cu LMM Auger spectrum confirmed that both Cu 0 and Cu + were present in A-CuNCs-1 as well.…”
Section: Resultsmentioning
confidence: 94%
“…Among these Cu‐based compounds, the chlorides of copper are mainly employed for traditional catalysis and have been less studied for electrocatalytic water splitting. They are mainly used as catalysts for methanol oxidation to prepare methyl carbonate or catalyzing cross‐coupling reaction [20,21] . In particular, copper(I) chloride (CuCl) not only can oxidize methanol, but also exhibits catalytic properties for the hydrolysis and dehydrogenation of BH 3 N 3 , this indicate that CuCl may have potential hydrogen catalytic activity as well as unique redox characteristics [22,23] .…”
Section: Introductionmentioning
confidence: 99%